New Media Convergence in Message Delivery Through Podcasts: An Analysis of Deddy Corbuzier’s Close The Door Podcast (Episode Case 003: Callous) - Muhammad Tabroni Tabroni; Marlina Marlina (PT Agung Media Publisher, 2025)
Media convergence has transformed the way messages are delivered, particularly in digital platforms such as podcasts. Deddy Corbuzier's Close The Door podcast is an example of how media convergence integrates audio and visual elements to enhance message delivery. This study aims to analyze how Deddy Corbuzier utilizes media convergence in episode Case 003: Callous and how the message delivery process takes place within this framework. This research employs a qualitative approach with a content analysis methodology. Data were collected through observations, interviews, and documentation to explore the strategies used in message delivery and audience engagement within the podcast. The findings indicate that Deddy Corbuzier applies video podcasting, which integrates audio-visual elements to create an immersive experience. The podcast facilitates two-way communication (interactional), enabling engagement between the host and the audience. The study also identifies key messages conveyed in the episode, such as the importance of self-confidence and avoiding the “people-pleaser” mentality. Additionally, the study highlights the success strategies suggested by Deddy Corbuzier, which include self-belief, perseverance, and continuous self-improvement. Deddy Corbuzier employs various communication techniques, including the bridging technique, which connects unrelated topics seamlessly to create engaging discussions. Furthermore, persuasive communication is utilized to influence audience perception and encourage motivation. The study suggests that media convergence in podcasts enhances storytelling effectiveness and audience retention.